Constructing "Composite Dialogs" from Qualitative Data: Towards Representing and Managing Diverse Perspectives - Peter G. Malvicini (Adult Education Research Conference, 1999)
During empirical research on adult learning, I developed a technical method of constructing dialogs from many interviews as an approach to qualitative data. Composite Dialogs present diverse perspectives while preserving elements of context and affect often lost through other methods. The approach should be of particular interest to adult educators who desire to link research to social action for democratic change.